2023
DOI: 10.1038/s41598-023-38568-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of endoplasmic reticulum stress-related gene signature for the prognosis and pattern in diffuse large B cell lymphoma

Chaofeng Zhang,
Qi Lin,
Chaoqi Li
et al.

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common lymphoma in adults. This study aimed to determine the prognostic significance of endoplasmic reticulum (ER) stress-related genes in DLBCL. ER stress-related genes were obtained from the molecular signatures database. Gene expression data and clinical outcomes from the gene expression omnibus and TCGA datasets were collected, and differentially expressed genes (DEGs) were screened out. Gene ontology enrichment analysis, the kyoto encyclopaedia of genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Using public databases ( 17 22 ), we found upregulated CISD2 as an appropriate diagnostic factors and a unfavorable prognostic indicator in DLBCL. Recent studies demonstrated that a clinical risk model included multiple genes is helpful to better implement the eligible diagnostic and the favorably prognostic criteria in DLBCL patients ( 52 55 ). Here, we developed a CISD2-related risk model (CISD2Risk) based on CISD2 related genes using LASSO Cox regression analysis in the GSE117556 dataset, and performed external validation (GSE181063 dataset) for its performance.…”
Section: Discussionmentioning
confidence: 99%
“…Using public databases ( 17 22 ), we found upregulated CISD2 as an appropriate diagnostic factors and a unfavorable prognostic indicator in DLBCL. Recent studies demonstrated that a clinical risk model included multiple genes is helpful to better implement the eligible diagnostic and the favorably prognostic criteria in DLBCL patients ( 52 55 ). Here, we developed a CISD2-related risk model (CISD2Risk) based on CISD2 related genes using LASSO Cox regression analysis in the GSE117556 dataset, and performed external validation (GSE181063 dataset) for its performance.…”
Section: Discussionmentioning
confidence: 99%